2010
DOI: 10.1186/cc9264
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary vascular and right ventricular dysfunction in adult critical care: current and emerging options for management: a systematic literature review

Abstract: IntroductionPulmonary vascular dysfunction, pulmonary hypertension (PH), and resulting right ventricular (RV) failure occur in many critical illnesses and may be associated with a worse prognosis. PH and RV failure may be difficult to manage: principles include maintenance of appropriate RV preload, augmentation of RV function, and reduction of RV afterload by lowering pulmonary vascular resistance (PVR). We therefore provide a detailed update on the management of PH and RV failure in adult critical care.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
265
0
7

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(274 citation statements)
references
References 355 publications
(314 reference statements)
2
265
0
7
Order By: Relevance
“…It is well known that acute PE can lead to RV dilation and failure, which predicts a worse prognosis (30,31 ). In contrast, several studies reported transient depression of RV systolic function and RV dilation after endurance sports without prognostic consequences (5,21,24 ).…”
Section: Biomarker Changes After Strenuous Exercisementioning
confidence: 97%
“…It is well known that acute PE can lead to RV dilation and failure, which predicts a worse prognosis (30,31 ). In contrast, several studies reported transient depression of RV systolic function and RV dilation after endurance sports without prognostic consequences (5,21,24 ).…”
Section: Biomarker Changes After Strenuous Exercisementioning
confidence: 97%
“…The cursor is placed to the junction of tricuspid valve plan with the free wall of the RV, whereas data are averaged over five beats (Figures 1 & 2). Normal values for TAPSE are 15-20 mm (Price et al, 2010;Meluzin et al, 2001;Lang et al, 2005). TAPSE calculation in a patient under spontaneous respiration by M-mode, using the 2D four-chamber view.…”
Section: Calculation Of Tapse In Cardiovascular Patientsmentioning
confidence: 99%
“…Clinically, patients with failing RV will present with reduced RV contractility, hypotension or end-organ dysfunction (Price et al, 2010). Results of a study conducted by Campo and colleagues in 2011 on outcomes of hospitalization for RHF, revealed high mortality rates and poor prognosis associated with the development of RHF in PAH patients.…”
Section: Right Ventricular Dysfunctionmentioning
confidence: 99%